Two Sisters with Idiopathic Pulmonary Hemosiderosis. Issue 8 (2007) - Gencer, Mehmet; Ceylan, Erkan; Bitiren, Muharrem; Koc, Ahmet
Abstract : Idiopathic pulmonary hemosiderosis (IPH) is a rare cause of diffuse alveolar hemorrhage with unknown etiology. In the present report, the presentations of two sisters are described: one sister had IPH, eosinophilia and a high serum immunoglobulin E (IgE) level; and the other had IPH, pneumothorax, eosinophilia and a high serum IgE level. Both cases had quite unusual presentations. The first patient was 23 years of age, and had suffered from dry cough and progressive dyspnea for four years. Her hemoglobin level was 60 g/L, total serum IgE level was 900 U/mL and eosinophilia was 9%. Her chest radiography revealed diffuse infiltration. She died due to respiratory failure. The second patient was 18 years of age. She had also suffered from dry cough and gradually increasing dyspnea for two years. She had partial pneumothorax in the right lung and diffuse infiltration in other pulmonary fields on chest radiography. Her hemoglobin level was 99 g/L, total serum IgE level was 1200 U/mL and eosinophilia was 8%. IPH was diagnosed by open lung biopsy. All these findings suggested that familial or allergic factors, as well as immunological factors, might have contributed to the etiology of IPH.